2013
DOI: 10.26641/2307-0404.2013.4.21528
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of modern range of fungicides and scope of their application in agriculture of Ukraine as component of state social and hygienic monitoring.

Abstract: Estimation of modern range of fungicides and scope of their application in agriculture of Ukraine as component of state social and hygienic monitoring. Vavrinevych O.P., Omelchuk S.T., Bardov V.G. The analysis of the range of pesticides, including fungicides, authorized for use in Ukraine and the scope of their application during 1999-2012 years was carried out. Statistical research methods were used in the analysis, evaluation of the results was carried out in terms of the rate of growth and increase. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Their range is permanently changing: preparations that cause long-term environmental consequences are excluded, and the list is supplemented with effective combinations of new, safer formulations with different action mechanisms (Khodakivska et al, 2017). It has been shown that amongst modern fungicides the largest share is made up by mixed preparations (26.3-39.3%) (Vavrinevych et al, 2013;Haq et al, 2020). When conducting social-hygienic monitoring, preparations of groups of strobilurins, triazoles, benzimidazoles, imidazoles, derivatives of inorganic compounds are priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their range is permanently changing: preparations that cause long-term environmental consequences are excluded, and the list is supplemented with effective combinations of new, safer formulations with different action mechanisms (Khodakivska et al, 2017). It has been shown that amongst modern fungicides the largest share is made up by mixed preparations (26.3-39.3%) (Vavrinevych et al, 2013;Haq et al, 2020). When conducting social-hygienic monitoring, preparations of groups of strobilurins, triazoles, benzimidazoles, imidazoles, derivatives of inorganic compounds are priority.…”
Section: Introductionmentioning
confidence: 99%
“…When conducting social-hygienic monitoring, preparations of groups of strobilurins, triazoles, benzimidazoles, imidazoles, derivatives of inorganic compounds are priority. To date, the use of fungicides with high activity at low doses is urgent (Vavrinevych et al, 2013). However, it should be taken into account that fungicides, as physiologically active substances, in addition to their direct actionthe protection of crops from pathogensalso affect the plant itself, influencing on the course of physiological and biochemical processes (Kuryata et al, 2017;Srivastava et al, 2020;Amaro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%